2016
DOI: 10.1177/1464420716653422
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of machining characteristics in rotary ultrasonic machining of quartz ceramic

Abstract: Quartz ceramic has been well observed as one of the highly demanded advanced ceramics which is receiving enlarging industrial approbation owing to its excellent and superior properties. However, its fruitful processing with traditional and non-traditional machining methods is still a challenge. The current article has aimed to experimentally investigate the influence of several process variables, namely, spindle speed, feed rate, coolant pressure, and ultrasonic power on machining characteristics of interest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…This methodology is particularly based on the advanced theory of graphs, and therefore its applications are very well renowned. The demonstration through graph "or" digraph model has proven to be useful for modeling and analyzing numerous varieties of systems and problems in numerous fields of science and technology [7][8][9]. The approach based on the matrix method is useful in analyzing the graph/digraph models expeditiously to derive the system function and index to meet the objectives.…”
Section: Basic Overview Of Graph Theorymentioning
confidence: 99%
“…This methodology is particularly based on the advanced theory of graphs, and therefore its applications are very well renowned. The demonstration through graph "or" digraph model has proven to be useful for modeling and analyzing numerous varieties of systems and problems in numerous fields of science and technology [7][8][9]. The approach based on the matrix method is useful in analyzing the graph/digraph models expeditiously to derive the system function and index to meet the objectives.…”
Section: Basic Overview Of Graph Theorymentioning
confidence: 99%
“…A conventional diamond cutting method aided with ultrasonic vibration has come into existence in the form of hybrid machining method called rotary ultrasonic machining (RUM) in which a high frequency oscillating and rotary metal bonded diamond core drill tool enables it to machine hard and complex materials (i.e., ceramic, super alloys, titanium, etc.). In addition, no heat treated/affected zone is created after machining with RUM process (Singh and Singhal, 2016a;Abdo et al, 2013;Feng and Xu, 2012). The effective trial of RUM process as an ultrasonic milling was carried out by Pei et al in 1995. The application of this hybrid method was extended to the drilling, grinding and face milling of ceramics with preliminary experiments.…”
Section: Machining Of Nickel-based Super Alloysmentioning
confidence: 99%
“…The highest MRR was obtained at a combination of high power rating and coarse grit size. Singh and Singhal (2016a, 2016b, 2016c investigated the machining characteristics of Al 2 O 3 and quartz ceramic by employing an experimental design approach through response surface methodology (RSM) and concluded that higher feed rate gives the best solution with respect to MRR. Increased spindle speed leads to an increase in the volume of indentation proportionally, which further caused higher MRR.…”
Section: Machining Of Nickel-based Super Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering its contributions to environmental hazards, chemical machining [13,14] is not considered as an environmentally friendly process. Other non-contact processes such as laser machining [15,16,17,18], plasma machining [19,20], electron beam machining [21,22,23], electrochemical machining [24,25,26,27], ultrasonic machining [28,29,30,31,32], and abrasive water jet machining [33,34,35,36,37] also have their advantages and disadvantages as reported by different researchers. Therefore, non-contact machining processes have received more attention considering they employ no-force machining as well as recognize the brittleness of the ceramic materials.…”
Section: Introductionmentioning
confidence: 99%